2022
DOI: 10.1007/s00011-022-01672-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of ferroptosis and relevance to inflammation

Abstract: Introduction Inflammation is a defensive response of the organism to irritation which is manifested by redness, swelling, heat, pain and dysfunction. The inflammatory response underlies the role of various diseases. Ferroptosis, a unique modality of cell death, driven by iron-dependent lipid peroxidation, is regulated by multifarious cellular metabolic pathways, including redox homeostasis, iron processing and metabolism of lipids, as well as various signaling pathways associated with diseases. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 169 publications
0
25
0
Order By: Relevance
“…Recently, increasing studies have suggested that proinflammatory cytokines serve as the connection between ferroptosis and inflammation 37,38 . TNF‐α can be implicated in the process of ferroptosis through regulating GSH and iron metabolism 39–41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing studies have suggested that proinflammatory cytokines serve as the connection between ferroptosis and inflammation 37,38 . TNF‐α can be implicated in the process of ferroptosis through regulating GSH and iron metabolism 39–41 .…”
Section: Introductionmentioning
confidence: 99%
“…While, TNF‐α triggers ferroptosis of keratinocytes through promoting the accumulation of ROS, MDA, and iron 44 . It is well established that ferroptosis aggregates inflammation through the release of proinflammatory molecules 37 . Ferroptosis is often accompanied by increased serum levels of TNF‐α 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is accompanied by the release of proinflammatory molecules, such as interleukin (IL)-1β and IL-18 ( Sun et al, 2020 ). Meanwhile, ferroptosis exacerbates the inflammatory response to varying degrees through mediators such as ferroptosis regulators like glutathione peroxidase 4, reactive oxygen species, lipoxygenases, and inflammatory mediators produced during ferroptosis ( Deng et al, 2022 ). Several anti-inflammatory drugs have been shown to inhibit ferroptosis in certain cellular models ( Wang et al, 2023 ).…”
mentioning
confidence: 99%
“…Many inflammatory diseases are associated with ferroptosis, such as acute renal failure, Acute lung injury, neurodegenerative diseases, chronic autoimmune diseases of the gastrointestinal, etc. ( Deng et al, 2022 ). A review by Zhang et al reported that inflammatory-associated intestinal diseases are strongly associated with ferroptosis, indicating that ferroptosis may act as potential therapeutic targets for inflammatory-associated intestinal diseases.…”
mentioning
confidence: 99%
“…Several publications have reported that ferroptosis is associated with liver disease ( Wu et al, 2021 ; Luo et al, 2021 ). The underlying mechanisms may be related to inflammatory responses, too ( Deng et al, 2022 ). The present Research Topic is comprised of five primary articles and three evaluations that center on the Research Topic of PCD.…”
mentioning
confidence: 99%